Da reestruturação produtiva iniciada na década de 1990 à produção da Base Nacional Comum Curricular - Quevedo, Emanuelle Aline Iung Teles (2021)
The dissertation “From the productive restructure that started in the decade of 1990s to the production of the Brazil's national common curricular base” which was presented to the Post Graduation Course in Education at Unioeste – Cascavel Campus, in the research line Education, Social Politics and Education, has as a main goal to comprehend the production movement of the Brazil’s national common curricular base - BNCC as a component of the productive restructure movement that started in the decade of the 1990s.The theme calls our attention once that during the last years we could observe more private institutions acting in the public education doing that through partnerships, didactic material, consultancies or even with teacher’s degree, what stimulated us to search for understanding how the process of the BNCC document formulation occurred. Considering the implementation process of the new Brazil’s common curricular base, in which there was a significant mobilization of the civil sectors that are connected to the economy, we considered expatiating upon the BNCC elaboration and the different interests that were considered during its production, association the BNCC to the productive restructure that started in the decade of the 1990s.The specific objectives of this research are: a) to comprehend the demand of the productive restructure process that started in Brazil in the decade of 1990s; b) to analyze the relations that motivated the production of the BNCC, based on the academic production about the theme; c) to investigate the possible relations between the BNCC production movement and the productive restructure movement. All these objectives were analyzed based on the study of the bibliographic and documentary research. To summarize it, as an analysis result we comprehend that the socio-emotional competences that were proposed by the BNCC are the element that connect the two movements that were mentioned before, either in the guidance of the international organisms for the economic restructure implemented in the decade of 1990s, or in the BNCC itself, the concepts and abilities/competences are highlighted, what indicates the relation between the production of the BNCC and the productive restructure.